Charlie and the great glass elevator - Dahl,Roald (Great Britain: Penguin Random House UK, 2022)
Charlie and the Great Glass Elevator is the sequel to Charlie and the Chocolate Factory. The story picks up immediately where the first book left off, with Charlie Bucket, his family, and Willy Wonka inside the Great Glass Elevator, soaring above the Earth. What begins as a magical journey quickly turns into an unexpected space adventure. When the Elevator accidentally blasts into orbit, the group finds themselves docking with a space hotel, where they encounter a new threat: vicious alien creatures called Knids. With Wonka$1 (Bs clever thinking and Charlie$1 (Bs bravery, they manage to escape and return safely to Earth. Back at the chocolate factory, new adventures continue$1 (Bincluding Wonka helping Charlie$1 (Bs grandparents become young again through a series of experimental age-reversing pills, which leads to more humorous and chaotic situations. The book is filled with Roald Dahl$1 (Bs signature style$1 (Babsurd humor, wild imagination, and satirical commentary on society. While not as focused or universally loved as its predecessor, it still offers a quirky and entertaining continuation of Charlie's fantastical journey with Mr. Wonka.s
Charlie and the Great Glass Elevator is the sequel to Roald Dahl$1 (Bs classic novel Charlie and the Chocolate Factory. Published in 1972, the book continues the adventures of Charlie Bucket and the eccentric inventor Willy Wonka. Unlike the first book, which is primarily set inside the chocolate factory, this sequel ventures into space and back again, combining elements of science fiction, fantasy, and satire. The story features imaginative settings, bizarre creatures (like the shape-shifting Vermicious Knids), and humorous social commentary, particularly poking fun at politics, bureaucracy, and vanity. Though less structured than its predecessor, the book retains Dahl$1 (Bs playful tone, creative wordplay, and moral undertones. It is best suited for middle-grade readers and fans of Dahl$1 (Bs other whimsical tales. While not as universally acclaimed as the first installment, it remains an important part of the Charlie series and showcases Dahl's boundless creativity and irreverent humor.s
Keywords: Science fiction adventure; Space travel